Pengaruh Penerapan Standar Akuntansi Pemerintahan (Psap) Terhadap Kecenderungan Fraud Dengan Akuntabilitas Kinerja Perangkat Daerah Pemerintah Sebagai Variabel Intervening (Studi Kasus Pada Perangkat Daerah Pemerintah Sulawesi Tengah) - Nur Chairunnisa A. Tantu; Moh. Noviar Lawasa; Wahyu Wunanto (Journal of Innovative and Creativity, 2025)
This study examines the influence of Government Accounting Standards (PSAP) implementation on fraud tendency through performance accountability of regional government apparatus as an intervening variable. Conducted at regional government organizations in Central Sulawesi province, this quantitative research employs structural equation modeling using WarpPLS 7.0. The findings demonstrate that PSAP implementation has a significant negative effect on fraud tendency (coefficient: -0.28, p<0.01), and a significant positive effect on performance accountability (coefficient: 0.27, p<0.01). Additionally, performance accountability significantly reduces fraud tendency (coefficient: -0.32, p<0.01), functioning as a partial mediator in the relationship between PSAP and fraud tendency. The model fit indicators confirm the robustness of the theoretical framework (APC=0.331, ARS=0.592, GoF=0.150). These results indicate that consistent adherence to PSAP strengthens performance accountability and establishes robust internal controls, thereby minimizing fraud risk in regional financial management. The integration of PSAP implementation and performance accountability reinforcement constitutes a fundamental foundation for achieving good governance and fraud prevention in government organizations.